2007
DOI: 10.1097/01.mcg.0000225666.46050.78
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Failed Colonoscopy in Nonagenarians

Abstract: Colonoscopy in nonagenarians is a safe procedure; however, it carries a significantly higher failure rate. Functional decline was found to be a significant predictive factor for failed colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…57 Also, failure to successfully complete a colonoscopy is reported to be higher in older patients. 14,58,59 However, among our included studies, there were scant adverse outcome data present to make meaningful comparisons between older and younger patients and these potential factors.…”
Section: Discussionmentioning
confidence: 99%
“…57 Also, failure to successfully complete a colonoscopy is reported to be higher in older patients. 14,58,59 However, among our included studies, there were scant adverse outcome data present to make meaningful comparisons between older and younger patients and these potential factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the very elderly population, several large studies have shown successful colonic preparation is more difficult to achieve despite patient compliance, tolerance, and the type of preparation used. [16][17][18] Poor preparation may be related to redundant colon length, intolerance to the volume of preparation, decreased autonomic innervation of the bowel, and colonic tortuosity. Another concern is the urgency with fecal incontinence and a higher risk of falls and fractures while getting to the bathroom, an event that can be avoided with proper planning and preprocedure assessment.…”
Section: Bowel Preparationmentioning
confidence: 98%
“…Although colonoscopy is undeniably the most accurate procedure for polyp and cancer detection, its overall sensitivity in the elderly is reduced by a relatively high rate of incomplete examinations, with caecal intubation having been shown to fail in nearly 40% of very elderly patients [7]. Colonoscopy feasibility in the elderly is further reduced by a decrease compliance to bowel preparation, mainly because of associated co-morbidities such as Parkinson's disease, cardiovascular, pulmonary or diabetes [8,9].…”
mentioning
confidence: 98%